2022
DOI: 10.3390/admsci12030111
|View full text |Cite
|
Sign up to set email alerts
|

Nationality Diversity in Corporate Boards and Tax Avoidance: Evidence from Oman

Abstract: We examine the impact of nationality diversity in corporate boards on tax avoidance by assessing whether foreign directors play monitoring or advisory roles. We use a sample of 1049 firm-year observations from companies listed on the Muscat Stock Exchange between 2009 and 2019. We find that board nationality and audit committee nationality are associated with lower effective tax rates, which equated to more tax avoidance (an advisory role). Our findings offer an important implication for policymakers who are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…However, the result shows a negative impact between supervisory boards and the performance of accounting aspect as measured by ROA). This finding is consistent with a prior study by Alshabibi et al (2022), who found that a nationality diversity board will lead to lower effective tax rates.…”
Section: Performance Of Accounting Aspect Return On Assets (Roa)supporting
confidence: 93%
See 4 more Smart Citations
“…However, the result shows a negative impact between supervisory boards and the performance of accounting aspect as measured by ROA). This finding is consistent with a prior study by Alshabibi et al (2022), who found that a nationality diversity board will lead to lower effective tax rates.…”
Section: Performance Of Accounting Aspect Return On Assets (Roa)supporting
confidence: 93%
“…Therefore, they will supply comprehensive culture capital, skill sets, and informational resources. Alshabibi et al (2022) bear in mind that foreign director members are more effective and independent in overseeing management than domestic directors. According to Choi et al (2012), foreign directors are comparatively split from majority shareholders because they are not a portion of the conventional local cronyism of school relationship, kinship, and regionalism with the significant part of owners.…”
Section: Nationality Diversitymentioning
confidence: 99%
See 3 more Smart Citations